Per Cantum: A digital tool for the teaching of virtual choir in e- learning - Amato, Daniel Chris; Hirago, Cynthia Yukiko (Revista Hipótese, 2021)
This work presents a digital tool for the teaching of vocal practices, in particular, for the discipline of Choral Singing, for the careers of degree in music in the modality of E-learning. The work is justified based on the hypothesis that the vocal practice disciplines in music careers in E-learning present certain weaknesses due partly to the lack of exclusive digital tools for this purpose. This study presents the stage of developing a tool of this type based on the technologies available in Brazil, including in the context of Internet access, with average high bandwidth speeds available for the population. This product, called Per Cantum, a virtual environment of choral singing, is simulated to facilitate the learning of singing in a group at a distance, being able to be used in face-to-face courses and the context of leisure.